Integrative application of heavy metal–resistant bacteria, moringa extracts, and nano-silicon improves spinach yield and declines its contaminant contents on a heavy metal–contaminated soil - Eltahawy, Abdelsatar M. A. E.; Awad, El-Sayed A. M.; Ibrahim, Ahmed H.; Merwad, Abdel-Rahman M. A.; Desoky, El-Sayed M. (Frontiers in Plant Science, 2022)
Microorganisms related technologies are of alternative and traditional methods of metal recovery or removal. Here, we identified and described heavy metal-resistant bacteria isolated from industrial polluted soils collected from various sites at a depth of 0-200 mm. A total of 135 isolates were screened from industrial influenced soil. The three highest isolates resistant to heavy metals were selected as Paenibacillus jamilae DSM 13815T DSM (LA22), Bacillus subtilis ssp. spizizenii DSM 15029T DSM (MA3), and Pseudomonas aeruginosa A07_08_Pudu FLR (SN36). An applied experiment was conducted to test the effect of isolated heavy metals-resistant bacteria (soil application) as well as foliar spray with silicon dioxide nanoparticles (Si-NPs) and moringa leaf extract (MLE) on production, antioxidant defenses, and physio-biochemical characteristics of spinach plant grown on heavy metals contaminated soil. Bacteria and MLE or Si-NPs have been applied in single or combined treatments. The findings revealed that all single or combined additions increased (p <0.05) plant height, shoot dry and fresh weight, leaf area, number of leaves plant-1, photosynthetic pigments content, total soluble sugars, free proline, membrane stability index, ascorbic acid, relative water content, α tochopherol, glycine betaine, glutathione, and antioxidant enzyme activities (i.e., peroxidase, glutathione reductase, catalase, superoxide dismutase and ascorbate peroxidase) compared to the control treatment. However, application of bacteria and/or foliar spray with MLE or Si-NPs significantly decreased plant leaves content of contaminants (Fe, Mn, Zn, Pb, Cd, Ni, and Cu), malondialdehyde, electrolyte leakage, superoxide radical (O2•−), and hydrogen peroxide (H2O2). The integrative additions showed more significant effect than single applications. Our study suggests the integrative addition of Bacillus subtilis as a soil application and MLE as a foliar spray as a critical approach to increase spinach plant performance and reduce its contaminants content under contaminated soils conditions.